Mechanical properties of the lung during swimming - Deroanne, R.; Pirnay, F.; Dujardin, J.; Petit, J. M. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
Heavy muscular exercise sollicits the function of ventilation in such a way that, in some maximum exercises, the amount of oxygen taken up by the respiratory muscles, may constitute a limiting factor uring exercise (15, 12). During the swimming events, the subject breathes under particularly difficult conditions especially when he is not well trained. The horizontal position, water pressure on the body and the corresponding modifications of the breathing pattern, as well as the mechanic of breathing constitute supp1ew~ntary strains on respiratory function. Such restrictions possibly limit oxygen supply to peripheral muscles and reduce physical performances in water. The aim of our study was the measurement of the modifications of the pulmonary flow resistances and lung elasticity induced by submersion in water during swimming by breast stroke and by back stroke.